Personal Hygiene Training for Children with Intellectual Disability - Juhanaini, Juhanaini; Suherman, Yuyus; Wibowo, Setyo Wahyu (Angstrom Centre of Education, 2022)
This community service program activity is driven by a sense of responsibility to improve the personal hygiene abilities for children with intellectual disability. Limited intellectual abilities and adaptive behavior of mentally retarded children have an impact on the ability or skills in taking care, maintaining health and personal hygiene. Based on this phenomenon, there is a need with a qualified training both for children with intellectual disability and other adults such as parents and teachers. This activity is provided with the provision of knowledge and skills in the form of training for parents and teachers as well as for children themselves on how maintaining their personal health and hygiene. The result obtained from this activity is an increase in the knowledge of parentsand teachers on how to guide, maintain and improve the health of children with intellectual disability. Meanwhile, for children with intellectual disability gradually can make efforts in maintaining personal hygiene and health based on their own levels of ability.